1981
DOI: 10.1021/bi00517a008
|View full text |Cite
|
Sign up to set email alerts
|

Study of transfer ribonucleic acid unfolding by dynamic nuclear magnetic resonance

Abstract: Nuclear magnetic resonance (NMR) measurements of proton exchange were performed on yeast tRNAPhe, and in much less detail on Escherichia coli tRNAfMet, over a range of Mg2+ concentrations and temperatures, at neutral pH and 0.1 M NaCl. The resonances studied were those of ring nitrogen protons, resonating between 10 and 15 ppm downfield from sodium 3-(trimethylsilyl)-1-propanesulfonate, which partake in hydrogen bonding between bases of secondary and tertiary pairs. Methods include saturation--recovery, line w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 26 publications
7
46
1
Order By: Relevance
“…The imino protons can recover their magnetization after saturation by spin-lattice relaxation (magnetic contribution) and by exchange with unperturbed solvent water (chemical contribution). Previous studies on transfer RNA (11,23,24) and DNA fragments (13)(14)(15)(16)(17) have demonstrated that the magnetic contribution predominates below room temperature and has a small activation energy, whereas the chemical contribution predominates above room temperature and has a large activation energy. We have determined the temperature dependence of the saturation recovery lifetimes of the AATT 12-mer duplex and the TATA 12-mer duplex between 0C and 60'C, and these are tabulated in Table 1.…”
Section: Bmentioning
confidence: 98%
“…The imino protons can recover their magnetization after saturation by spin-lattice relaxation (magnetic contribution) and by exchange with unperturbed solvent water (chemical contribution). Previous studies on transfer RNA (11,23,24) and DNA fragments (13)(14)(15)(16)(17) have demonstrated that the magnetic contribution predominates below room temperature and has a small activation energy, whereas the chemical contribution predominates above room temperature and has a large activation energy. We have determined the temperature dependence of the saturation recovery lifetimes of the AATT 12-mer duplex and the TATA 12-mer duplex between 0C and 60'C, and these are tabulated in Table 1.…”
Section: Bmentioning
confidence: 98%
“…Inspection of the 1 H NMR spectra of the bacteriophage T2 and the frameshifting pseudoknots suggests that there are significant differences in the rates at which the imino protons within the base pairs exchange with solvent (Fig+ 4), particularly for those base pairs located at the junction of the pseudoknot stems+ The relationship between solvent exchange rate and dynamic features of RNA such as the opening frequency of base pairs can be quite complex+ When the base pair dissociation constant is much less than one, and the rate of imino proton exchange is significantly greater than the rate of base pair closing, the imino proton exchanges with solvent each time the base pair opens (referred to as an "EX1" mechanism)+ Alternatively, a base pair may open many times before proton exchange occurs; in this case the rate-limiting step is the base-catalyzed exchange with solvent+ The former mechanism has been observed in studies of tRNA (Hurd & Reid, 1980;Johnston & Redfield, 1981;Choi & Redfield, 1995) and a protein-DNA complex (Dhavan et al+, 1999), whereas the latter has been observed in several DNAs and drug-DNA complexes, in which case, the rate of base pair opening may be one to two orders of magnitude higher than the imino proton exchange frequency (reviewed by Guéron & Leroy, 1995)+ The observation of relatively rapid imino proton exchange for a particular base pair within an RNA structure therefore implies that either the base pair has a relatively rapid opening frequency or the efficiency of exchange is accelerated by the presence of a catalyst+ Imino proton exchange rates for the bacteriophage T2 pseudoknot and the representative frameshifting pseudoknots were estimated using a saturation transfer method+ For the bacteriophage T2 pseudoknot, imino proton exchange rates for the stem base pairs are all relatively slow, in the range of 0+8 to 4+2 Hz (Fig+ 8; ), and estimated imino proton exchange rates (K HX ) for guanosine N1 and uridine N3 imino groups within base-paired nucleotides+ Theta is the angle between the imino N-H bond vector and the major axis of inertia of the pseudoknot+ The imino resonances of G4 and G10 and G5 and G13 overlap in both the 1 H and 15 N dimensions; reported relaxation rates for these nuclei are for the composite (overlapping) peaks+ Table 3)+ Interestingly, the exchange rates of imino protons at the junction of the stems are not much different from those in the central regions of the stems+ In the SRV frameshifting pseudoknot (Fig+ 8; Table 4), exchange rates for most of the base-paired imino protons are in the range of 1 to 2 Hz, with the exceptions of G16 at the junction of the stems (;50 Hz), G3 at the end of stem 1 (;9 Hz), and U34 at the junction of the two stems (;300 Hz)+ In the VPK frameshifting pseudoknot and the hybrid frameshifting pseudoknot, the imino protons of the base pairs adjacent to the junction of the stems are unobserved, indicating solvent exchange rates of greater than 300 Hz+ The data therefore suggest that the opening frequency of the base pairs at the junction of the stems in the bacteriophage T2 pseudoknot is significantly slower than the corresponding base pairs in the frameshifting pseudoknots+…”
Section: Comparison Of Imino Proton Exchange Ratesmentioning
confidence: 99%
“…This appears to be a characteristic of all FUra-substituted tRNAs, and may indicate that peak A corresponds to an invariant base substituted by fluorouracil. Redfield and collaborators (Johnson and Redfield, 1981;Tropp and Redfield, 1981) have observed a resonance in the NMR spectra of several tRNAs that also exhibits a hypersensitivity to changes in Mg**. This peak has been assigned to the imino proton at N(l) of Y55.…”
Section: Ion Binding ^ Fura-substituted Trnamentioning
confidence: 99%
“…The thermal unfolding sequence of tRNA^he has recently been studied using imino proton exchange (Johnson and Redfield, 1981;Roy and Redfield, 1983 Reid (1981) where the anticodon helix melts before unfolding of tertiary structure occurs.…”
Section: Meltingmentioning
confidence: 99%
See 1 more Smart Citation